Kenya, Uganda, and United Republic of Tanzania : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This Selected Issues paper for Kenya, Uganda, and United Republic of Tanzania highlights their private sector credit markets, identifies their main obstacles in promoting credit to the private sector, and suggests a reform strategy. If the East African Community (EAC) countries decide to pursue a coordinated approach to investment incentives, one possible solution would be to agree on a Code of Conduct for Investment Incentives and Company Income Taxation. A transparent tax system with a broad base would reduce the demand by investors for tax holidays.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet